Pengaruh Koperasi Syariah terhadap Kemudahan Akses Modal bagi UMKM - Nugroho, Hussein Satrio; Nugroho, Aditya Febriansyah; Taqiyya, Savira Ihdha (Fakultas Ekonomika dan Bisnis, Universitas Diponegoro, Semarang, 2021)
One approach to alleviate poverty is by empowering Sharia Microfinance Institution one of this form is sharia cooperation (koperasi syariah). Sharia cooperative is a type of cooperative that provides economic welfare for its members according to Islamic norms and morals and also has other functon to create a brotherhood relation and justice in accordance to Islamic principles. Currently, many MSMEs are experiencing difficulties in accessing capital. The purpose of this study is to analyze the effect of Sharia cooperatives on access to capital for MSMEs. The conclusion of this research is sharia cooperation has significance role and influence in empowering micro small and medium enterprises (MSMEs) by providing financing to business actors in accordance with sharia principles. By doing so, hopefully MSMEs can access capital more easily to develop more.